Regional and Sub-Global Climate Blocs.A Game-Theoretic Perspective on Bottom-up Climate Regimes - Carlo Carraro; Barbara Buchner (Fondazione Eni Enrico Mattei (FEEM), 2005)
No international regime on climate change is going to be fully effective in controlling GHG emissions without the involvement of countries such as China, India, the United States, Australia, and possibly other developing countries. This highlights an unambiguous weakness of the Kyoto Protocol, where the aforementioned countries either have no binding emission targets or have decided not to comply with their targets. Therefore, when discussing possible post-Kyoto scenarios, it is crucial to prioritise participation incentives for all countries, especially those without explicit or with insufficient abatement targets. This paper offers a bottom-up game-theoretic perspective on participation incentives. Rather than focusing on issue linkage, transfers or burden sharing as tools to enhance the incentives to participate in a climate agreement, this paper aims at exploring whether a different policy approach could lead more countries to adopt effective climate control policies. This policy approach is explicitly bottom-up, namely it gives each country the freedom to sign agreements and deals, bilaterally or multilaterally, with other countries, without being constrained by any global protocol or convention. This study provides a game-theoretic assessment of this policy approach and then evaluates empirically the possible endogenous emergence of single or multiple climate coalitions. Welfare and technological consequences of different multiple bloc climate regimes will be assessed and their overall environmental effectiveness will be discussed.
Keywords: C72; H23; Q25; Q28; 330; Agreements; Climate; Incentives; Negotiations; Policy